Quick Evaluation Study on Fourteen (14) Major Development Programmes in 33 Selected Districts of the 8 States Affected by Left Wing Extremism (LWE) Volume-IV - Planning Commission (Planning Commission, 2012)
The present state of Chhattisgarh was carved out of Madhya Pradesh on 1st November, 2000. By population, it ranks as the 16th most-populated state of the nation and area-wise it is the 10th largest state in India, with an area of 135,190 km2 (52,200 sq mi). Chhattisgarh borders the states of Madhya Pradesh in the northwest, Maharashtra in the west, Andhra Pradesh in the south, Orissa in the east Jharkhand in the northeast and Uttar Pradesh in the north.
Reports on the State of Chhattisgarh and 7-LWE Districts: Bastar, Bijapur, Dantewada, Kanker, Narayanpur, Rajnandgaon and Surguja